Optimizing the Role of MSMEs in Driving Regional Economic Growth Through Digital Transformation and Local Technology-Based Innovation In Indonesia - Syamsu Rijal; Mustari (International Journal of Technology and Education Research, 2025)
This article aims to critically analyze how the strategy of optimizing the role of MSMEs in the digital economy ecosystem can encourage sustainable regional economic growth. This research uses a library research method, with narrative data analysis that emphasizes extracting, interpreting, and telling experiences or phenomena based on existing literature. The results show that optimizing the role of MSMEs in regional economic growth can be achieved through digital transformation and local technology-based innovation. Collaborative support from the government, private sector, and community is needed so that MSMEs are able to adapt, improve competitiveness, and create an inclusive and sustainable economy.